2006
DOI: 10.1002/lsm.20353
|View full text |Cite
|
Sign up to set email alerts
|

Time‐domain and spectral‐domain optical coherence tomography in the analysis of brain tumor tissue

Abstract: Spectral-domain OCT of experimental gliomas and human brain tumor specimens differentiates solid tumor, diffusely invaded brain tissue, and adjacent normal brain based on microstructure and B-scan signal characteristics. In conjunction with the rapid image acquisition rates of SD-OCT, this technology carries the potential of a novel intraoperative imaging tool for the detection of residual tumor and guidance of neurosurgical tumor resections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
78
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 23 publications
(25 reference statements)
2
78
0
3
Order By: Relevance
“…Such a qualitative link may verify that certain structures can be detected in both images, but remains indirect because it does not guarantee that each observed object or even the major part of it, indeed corresponds to, e. g., a brain cell. If the quantitative link between these novel images and fluorescence/H&E stained images can be established, it will facilitate and verify the interpretation of these novel images, and further strengthen their potential for real-time pathology of human brain tumors [6,21,24,25].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Such a qualitative link may verify that certain structures can be detected in both images, but remains indirect because it does not guarantee that each observed object or even the major part of it, indeed corresponds to, e. g., a brain cell. If the quantitative link between these novel images and fluorescence/H&E stained images can be established, it will facilitate and verify the interpretation of these novel images, and further strengthen their potential for real-time pathology of human brain tumors [6,21,24,25].…”
Section: Introductionmentioning
confidence: 93%
“…The active contour models [33][34][35][36][37][38][39][40][41][42][43] became popular for automatic cell/nuclei segmentation at the beginning of this century when the classical CV model [33] was proposed. THG images, with Raman and other nonlinear microscopy images, differ from labeled-fluorescence images in their complexity, inherent to their high information density [5,6,20,21,24,25,[44][45][46][47]62]. A limited number of segmentation methods has been explored on THG images of several tissue types.…”
Section: Introductionmentioning
confidence: 99%
“…Bizheva et al reported the first studies on ex vivo human tissues (65). Böhringer et al reported imaging of human brain tumor specimens using TD-OCT and SD-OCT system to identify tumor and normal tissue using optical characteristics (66)(67)(68). Due to the intrinsic optical property of brain tissue, near-infrared OCT has a deeper viewing field/range than visible light used in the OCT system (42,67-69).…”
Section: Identification Of Tumorous and Non-tumorous Tissue With Oct mentioning
confidence: 99%
“…confocal microscopy [15], multiphoton tomography (MPT) [16] and optical coherence tomography (OcT) [17,18] are of interest not only in respect of intraoperative identification of neoplasm boundaries, but also as methods for optical cytobiopsy.…”
Section: No4 65 сLinical Medicinementioning
confidence: 99%